Annexure - V To the Report of the Planning Group on Civil Aviation at the Turn of the Century - Planning Commission (Planning Commission, 1986)
It aught to be mentioned here that, whereas the aircraft prices generally reflect the value at the time of delivery, the support cost may not be accurate similar wise, since the supply of supporting material may be spread in time, and therefore experience a higher escalation. Also, additional tools and equipment are required at a later date, which essentially form a part of a particular time discreet project. Examples of this arc the additional spare parts and engine purchase for the A300 in 1984-85 and the recent acquisition of a simulator for the Boeing 737.
Consultant Planning Commission Government of India
Consultant Planning Commission Government of India